Implementing Visual Aids into Teaching English Vocabulary for Children: Perspectives from Teachers at Ho Chi Minh City - Tuong Thien Lac Nguyen (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2026)
The Vietnamese education system highly values English as a compulsory subject for schools at all levels. Regarding this increasing demand, English teachers are encouraged to come up with new approaches and strategies to make the English learning process faster and more enjoyable, and one solution is applying Visual aids (VA) in teaching English vocabulary to children. This study adopts a quantitative research design. Data were collected through a questionnaire survey administered to 62 participants, including university lecturers, secondary school teachers, primary school teachers, and teaching assistants in Ho Chi Minh City (HCMC). The questionnaire consisted of a Likert scale and one open-ended question to explore participants’ perceptions and challenges. The collected data were analyzed using descriptive statistics, including frequencies, percentages, means, and standard deviations. The findings show that VA is highly recommended by most participants; they claim that the benefits of using VA are undeniable. Several teachers share some of the challenges they encounter when implementing VA, even though most of the results collected are positive. This research concludes with some implications and recommendations for further studies.